ANALISIS PENGUKURAN KINERJA PT. JAPFA COMFEED INDONESIA TBK MENGGUNAKAN METODE SWOT BALANCED SCORECARD - ROKHIM FIRMANSYAH, MIFTAKHUL; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2017)
This study was aimed to analyze the performance of the company PT. Japfa Comfeed Indonesia, Tbk by four (4) perspectives in Balanced Scorecard which is, financial perspective, customer perspective, internal business process perspective, learning and growth perspective and decided strategy using SWOT. This research was held at PT. Japfa Comfeed Indonesia, Tbk Branch Office of Sidoarjo. The results of the research show that the financial performance from year to year was fluctuate but has a good performance in general. Meanwhile on the measurement of non-financial performance consisting of customer perspective, internal business processes customer perspective and growth and learning customer perspective had a good performance. Overall results of the PT. Japfa Comfeed Indonesia, Tbk companys performance using Balanced Scorecard was Good which is equal to 78,56%. Viewed from the Balanced Scorecard results and combined with the SWOT matrix author found some strategies that are expected to support PT. Japfa Comfeed Indonesia, Tbk.